The influence of logistics service quality on customer satisfaction and loyalty at Alfamart in Indonesia - Putu Melinda; Siti Rahayu; Adi Tedjakusuma (Faculty of Business and Economics, University of Surabaya, 2025)
This study aims to determine the relationship between logistics service quality, customer satisfaction, and loyalty in customers using Alfamart's BOPS shopping service through Alfagift. Data processing was carried out using SPSS 26 and SmartPLS 3. The data used in this study are primary data obtained from distributing questionnaires. Respondents in this study were 250 respondents who had used Alfamart's BOPS shopping service through Alfagift at least 2 times in the past 1 year. The sampling technique in this study was non-probability sampling. Based on the results of hypothesis testing, what affects customer satisfaction is timeliness, while what affects customer loyalty is availability. In this study, customer satisfaction is also significant in influencing customer loyalty.